The relationship between single parenting and children's behavior - Deborah Ikiriza (Uganda christian university, 2024)
Among the issues, the research was interested in understanding single parenthood and its inclusion on children behavior specifically for Nakawa division. The study purposively employed three main objectives; to assess the causes of single motherhood in Nakawa town, identify the roles played by parents in shaping child behavior among children within Nakawa Town and establish challenges mothers face while raising their children out of wedlock. Design The study used a cross-sectional approach with mixed quantitative and qualitative methodologies. Questionnaires and interview guide were used to collect data from 36 respondents. This data was subsequently analyzed using the statistical package for social scientists (SPSS) guide to R and SPSS Data Analysis. Reduced parental support was highlighted as a challenge that led to single motherhood in Nakawa town especially Least of the causes Single mothers get pregnant by mistake The increase in divorce cases has increased number of single mothers, Some mothers choose to become pregnant and take care on their own, Now days some women choose to adopt kids from streets or child care centers and take care of them, Due to domestic violence, many men decide to abandon their homes in hands of the mothers, Some mothers are single because their husbands died, Addiction to alcohol and drug abuse by the husband and Many men after sometime in marriage try to get second wives hence leaving behind their families. Likewise, the study concluded that the challenges single mothers face in raising children in Nakawa town included; financial challenges are significant struggle to many single mothers, the absence of emotional support leads to depression, anxiety and other mental issues, single mothers often face difficult choices when it comes to childcare as they need to balance the costs of childcare with their income from work, single mothers have to work long hours to provide for their children which makes it difficult to find time for other important responsibilities and single mothers face a challenge of finding and maintaining safe and affordable housing for themselves and their children. The study recommended that single mothers need to create time for themselves. Even if it’s something as simple as reading a book, taking a warm bath or having a chat with a friend, setting aside a little personal time will give her a chance to refuel. Even if it is only fifteen minutes, take time out of the week to do something for herself, and also going for a walk or writing in a journal-something that allows one to reconnect with what we were before we became parents.